2016
DOI: 10.1007/jhep12(2016)079
|View full text |Cite
|
Sign up to set email alerts
|

Improved jet substructure methods: Y-splitter and variants with grooming

Abstract: It has recently been demonstrated with Monte Carlo studies that combining the well-known Y-splitter and trimming techniques gives rise to important gains in the signal significance achievable for boosted electroweak boson tagging at high p t . Here we carry out analytical calculations that explain these findings from first principles of QCD both for grooming via trimming and via the modified mass-drop tagger (mMDT). We also suggest modifications to Y-splitter itself, which result in great simplifications to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…It has also seen many more recent developments, noticeably analytic studies of substructure observables (e.g. [10][11][12][13][14][15][16][17][18][19]), the use of substructure techniques to probe the quark-gluon plasma in high-energy heavy-ion collisions (e.g. [20][21][22][23][24]), the use of Machine Learning techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has also seen many more recent developments, noticeably analytic studies of substructure observables (e.g. [10][11][12][13][14][15][16][17][18][19]), the use of substructure techniques to probe the quark-gluon plasma in high-energy heavy-ion collisions (e.g. [20][21][22][23][24]), the use of Machine Learning techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…If we take for example the case of the mMDT, this prefactor would be largely suppressed for the background -going from ∼ α s log(1/ρ) for full N -subjettiness to ∼ α s log(1/z cut ) for the dichroic method -while the signal would only be suppressed by a much smaller factor ∼ 1 − 2z cut . Additionally, measuring the tagged jet mass instead of the full jet mass significantly reduces ISR and non-perturbative effects which would otherwise affect the resolution of the signal mass peak (see also [28,29]). …”
Section: Jhep03(2017)022mentioning
confidence: 99%
“…To complete our Monte Carlo studies, in figure 13 we compare the performance of τ dichroic 21,groomed with various other tools: mMDT tagging alone, SoftDrop grooming alone (β = 2 as above), and also the Y m variant [29] of Y-splitter [43], combined either with SoftDrop (pre-)grooming or with trimming [44], as described in detail in ref. [29] (see also ref.…”
Section: Brief Comparison With Other Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in jet substructure (see [36] for a recent review) have shown that the modified mass drop tagging algorithm (mMDT) or soft-drop grooming procedure robustly removes contamination from both underlying event and non-global color-correlations, see Refs. [21,22,37], and have been applied to study a wide variety of QCD phenomenology within jets [38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%